Moral and Personality Development in the Perspective of the SDGs: A Critical Analysis of Kohlberg’s Theory and Its Implementation in Junior High Schools - William Jasson Ngangi; Mukh Nursikin; Badrus Zaman; Muhammad K. Ridwan (Profetika: Jurnal Studi Islam, 2024)
Objective: This study explores the implementation of moral and personality development within the framework of the Sustainable Development Goals (SDGs) by analyzing the application of Kohlberg’s moral development theory through project-based learning in junior high schools in Purworejo, Central Java. The main objective of this research is to examine how project-based learning, as part of the independent curriculum, fosters students’ moral and personality growth. Theoretical framework: The theoretical framework is based on Lawrence Kohlberg’s stages of moral development, emphasizing the importance of moral reasoning in shaping ethical behaviour. Literature review: A literature review reveals that integrating moral education into formal curricula, particularly through experiential learning, can enhance students’ capacity for critical thinking, ethical decision-making, and personal responsibility—elements essential for achieving the SDGs in education. Methods: A qualitative descriptive method was employed, using observation, interviews, and documentation for data collection. Data analysis followed the steps of data reduction, data display, conclusion drawing, and verification. Results: The research findings indicate that at SMP Negeri 40, moral and personality development was effectively nurtured through democratic election projects (OSIS and MPK) and a local food processing initiative. Similarly, SMP Sultan Agung Purworejo applied the IPNU and IPPNU election projects, as well as a local cultural project titled Kitab Ngudi Susilo, to instil moral values and cultural awareness. Implications: The implications of this study suggest that contextual, project-based learning strategies are successful in aligning educational outcomes with the moral and personality competencies targeted by the independent curriculum and the SDGs. Novelty: The novelty of this research lies in the contextual application of Kohlberg’s theory within the Indonesian junior high school setting, highlighting how project-based learning can bridge theory and praxis in moral education.